Myths and misconceptions regarding contraception in the urban poor community in Jamshedpur, India - Tiwari, Pushpa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Family planning, a basic human right endorsed by the United Nations, allows everyone to decide the number, spacing and timing of their children. This leads to fewer complications related to pregnancy and childbirth, improves overall health. Despite the obvious benefits, because of deeply rooted myths and misconceptions, they do not access these services. Methods: Study was conducted in 10 Maternal and Child Health centers run by Tata Steel Family Initiatives Foundation in and around Jamshedpur in Jharkhand, India. The study is based on primary quantitative data. Data collection was by interviewing the respondents using a questionnaire. Results: A total of 500 respondents were interviewed. Out of 500 respondents 392 were women and 108 were men. The concept of family planning was well known. 99% women while 100% men had heard about family planning. Only 49 % women and 45% men had correct knowledge regarding spacing between two children. 78% women and men had correct knowledge about dual benefits of condom use. 63% women and 64% men feel that Cu T causes backache and pain abdomen, hence they avoid using it. 54% women and 51% men do not like OCP as a method of family planning as it is difficult to take it daily. Around 45% women and men were afraid regarding Tubectomy/ LTT. More women (41%) than men (38%) think that NSV causes weakness. Again, more women (36%) than men (34%) think that NSV decrease capacity to do heavy work. Conclusions: Results are showing that only knowledge about contraception is not enough to increase usage. Behaviour change communication activities are needed to provide accurate information to dispel common myths and misconceptions about modern contraceptives.